The Influence of Celebrity Endorsements, Brand Image and Price Perceptions on Erigo Product Purchase Decisions by Students of the Faculty of Economics and Business UPN "Veteran" East Java - Raisha Dellania Widiyan; Siti Aminah (Jurnal Ekonomi dan Bisnis Digital, 2023)
Muhammad Sadad launched the local clothing brand Erigo in 2011. Erigo manufactures a variety of goods, including apparel, purses, jeans, and coats. This research attempts to ascertain how celebrity endorsers, brand perception, and pricing perception affect students at the Faculty of Economics and Business UPN "Veteran" East Java's choices to buy Erigo products. In this work, structural equation modeling (SEM) and the analytic program partial least squares (PLS) were used for data analysis.  According to the study's findings, celebrity endorsements, brand image, and pricing perceptions all have a favorable and substantial impact on consumers' decision-making.